MENGAPA INOVASI DIBUTUHKAN DALAM PENENTUAN PRIORITAS KEBIJAKAN ANGGARAN DESA - Shadu Satwika Wijaya (Jurnal Inovasi Daerah, 2022)
A village's budgeting process is crucial to the village's overall financial cycle. Research on public budgeting is urgently needed because democratization necessitates transparency regarding the utilization of village transfer funds. According to the findings of previous research, the village government's budgeting performance has been quite optimal in terms of the planning, implementation, and budget utilization processes. There are still conditions that are not yet aligned between priorities and budget allocations to preferences for basic service needs for the community. However, the good performance of this budgeting has not been matched by efforts to prioritize the basic service needs of rural communities. This study analyzes the data using the theory of actor relations in public policy as a result .The research was done using a qualitative method, and the locations of the study were 24 randomly selected villages in the Cilacap Regency. Stakeholders in the development of village-level budgeting policies are the focus of this study. Focus Group Discussion (FGD) was used to gather data. According to the findings of this study, there is a disconnect between the activities program included in the Village Government Budget (APBDes) and the requirements of the village community. At the village government elite level, there was little discussion following the aspirations screening.